(untitled) (Theatrum historiae, 2024)
This article describes the history and rituals of the Bavarian Order of St. George as a member of the Austrian aristocracy, Eduard (Odoardo) III Collalto, experienced them in 1802–1803, when he entered the order and made his way through its ranks from a Knight through a Commander to the highest rank of the Grand Commander. It first describes the history of the order and then it continues to the history of the House of Collalto, after which it describes the ceremonies Count Eduard Collalto experienced. The possible reasons why the aristocrats of the Habsburg monarchy entered the order of the Bavarian Elector are also considered. In conclusion it offers two possible reasons why Count Collalto joined the order; the confirmation of his nobility, which the Order offered, and possible hesitation regarding serving the Austrian Emperor after Venice, where Count Collalto had started a promising career, had been annexed to the Austrian Empire in 1797.